PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS QUIZIZZ MATERI PARAGRAF PADA MAHASISWA TEKNIK MESIN POLITEKNIK NEGERI SRIWIJAYA - Ries Tuti, Resti; Revie Juniarti; Bhramastya Sandy Hargita; Novritika; Sri Wahyuni (Jurnal Korpus, 2025)
The quality of learning can be improved by using digital learning media. This study aims to develop a Quizizz-based learning media for paragraph material for students. This research is a research and development (R & D) with the ADDIE model including Analysis, Design, Development, Implementation and Evaluation. The stages in this study are design, development and implementation. The analysis stage is to analyze the needs of Quizizz-based learning media for paragraph material. The design stage is to create a Quizizz-based learning media product for paragraph material. The development stage is to compile questions that will be integrated with paragraph material in Quizizz-based learning media, conducting product validation with media experts, linguists, and material experts. The implementation stage is to apply Quizizz-based learning media for paragraph material to students during Indonesian Language lectures. The research subjects used students of the D3 mechanical engineering program at Sriwijaya State Polytechnic. The findings of this study are in the form of a product in the form of Quizizz-based learning media for paragraph material that is very valid and can be used for Indonesian Language lectures.